2022
DOI: 10.3390/ijerph19116438
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Access to WASH in Urban Schools during COVID-19 in Kazakhstan: Case Study of Central Kazakhstan

Abstract: The WHO/UNICEF Joint Monitoring Program (JMP) for Water Supply, Sanitation and Hygiene (WASH) produces global estimates of the real situation of access to water, sanitation and hygiene services, and sanitation and hygiene in households, educational institutes and health care facilities; however it is lacking data on schools in Kazakhstan. Thus, the aim of this research was to assess access to WASH in schools of urban area in Kazakhstan. The study was conducted in seven schools of Central Kazakhstan during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…This is in line with the theory of planned behavior (control beliefs) that explains that if facilities are available, it can positively influence human behaviors [11][12][13]. In addition, a previous study revealed that providing water and related services in schools can address the spread of COVID-19 [16]. The Veronica Buckets is a low-cost device which can be easily made available in all the schools in Ghana to improve hand washing hygiene and subsequently the spread of diseases such as COVID-19.…”
Section: Association Between Hand Washing Practice Andsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in line with the theory of planned behavior (control beliefs) that explains that if facilities are available, it can positively influence human behaviors [11][12][13]. In addition, a previous study revealed that providing water and related services in schools can address the spread of COVID-19 [16]. The Veronica Buckets is a low-cost device which can be easily made available in all the schools in Ghana to improve hand washing hygiene and subsequently the spread of diseases such as COVID-19.…”
Section: Association Between Hand Washing Practice Andsupporting
confidence: 80%
“…According to Bolon [15], a lack of understanding of personal hygiene, adherence, and behaviors toward proper hand hygiene all contribute significantly to the prevalence of communicable diseases COVID-19 inclusive-which has a negative impact on the long-term development of schoolchildren. In Kazakhstan, Toleubekovet al [16] undertook their study to evaluate WASH access in urban schools within the COVID-19 pandemic era amidst the observance of preventive procedures. They note that providing water and related services in schools not only addresses the spread of COVID-19, but also tackles the achievement some SDG targets especially SDGs 4 and 6.…”
Section: Theoretical Underpinning and Empirical Literature Reviewmentioning
confidence: 99%
“…The results in table 3 has shown that the Almajiri schools surveyed 3.3% have basic sanitation (improved sanitation facilities at the school that are single-sex and usable at the time of the visit); 6.7 % limited sanitation (Improved sanitation facilities at the school that are not single-sex or not usable at the time of the visit); and most of them (90.0%) have no service at all (unimproved sanitation facilities or no sanitation facilities at the school). Low sanitation was noticed in this study, in conflict with an urban study from, that revealed improved sanitation services in the schools observed in Kazakhstan (Toleubekov et al, 2022). Similar to this study results in table 2, there was a related challenges of WASH in a Ghana community including inadequate toilets, and handwashing facilities (Mensah al., 2022).…”
Section: General Remarksupporting
confidence: 78%
“…42 All schools in Addis Ababa had drinking water and 99% of children had access to it, which was higher than the MoE's reported 68.5%, and only 58.2% of disabled students had access to it, which was better than the MoE's reported 40.4% in primary and 32.6% in secondary, and studies done in Kazakhstan showed that 53.2% of school students had access to drinking water. 29 However, this study is smaller than the one conducted in South Wollo, where 62.5% of water points are accessible to children with disabilities. This could be because in Addis Ababa schools, student consultation and stakeholder participation during the design and construction of WASH facilities at all levels were extremely low.…”
Section: Discussionmentioning
confidence: 76%
“…Data on the status of school WASH services were collected using a structured questionnaire adapted from the JMP and observing on-site using observational checklist. 22,[29][30][31] The school directors provided information about the school's WASH facilities and services, which was cross-checked using observational checklists. The data were collected by 4 trained environmental health officers with bachelor's university degree.…”
Section: Data Collection Methodsmentioning
confidence: 99%